2019
DOI: 10.22460/project.v2i3.p319-324
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception of Using “Dictionary Pocket” as a Medium to Improve Their Vocabulary Mastery

Abstract: Vocabulary known as an essential skill for learning to read, speak, write and listen. It is important to find the appropriate technique in order to improve students’ vocabulary mastery. The researchers did research with focuses on students’ perception towards using “dictionary pocket” in order to improve their vocabulary mastery. It was conducted using a qualitative descriptive method. To collect the data, the researchers use the instruments of an open-ended questionnaire and interview section. The samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The result of questionnaire also showed that most of the students agreed that the flashcards are helping them in memorizing new vocabulary. Same as the previous study that also found that flashcard helm in memorize the vocabulary (Farida, Isrina, & Apsari, 2019).…”
Section: Discussionmentioning
confidence: 54%
“…The result of questionnaire also showed that most of the students agreed that the flashcards are helping them in memorizing new vocabulary. Same as the previous study that also found that flashcard helm in memorize the vocabulary (Farida, Isrina, & Apsari, 2019).…”
Section: Discussionmentioning
confidence: 54%
“…However, this condition does not only happen in students of Informatics Engineering. The same problem in language learning was also found in 2019 about the lack of vocabulary of the students effectively solved by using a pocket dictionary as the medium of learning (Mariah et al, 2019); this strategy is effective in engaging students' motivations to learn English more since the pocket dictionary was successfully built autonomy for the students and also helped students to be more confident using the word they have already known as well as help them to uncover the unknown word.…”
Section: Discussionmentioning
confidence: 74%
“…The other research also showed that most students are rarely interested in using dictionaries (Mariah et al, 2019). On the contrary, they prefer to use Google Translate or translate machines as an online dictionary rather than memorizing words from dictionaries or printed materials (Mariah et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the findings of the research, it has been concluded that flashcards prove to be helpful in increasing vocabulary as the null hypothesis has been rejected because the significance level is been above 0.05. Farida, Isrina & Apsari (2019), have done research work to enhance the EFL vocabulary mastery of the learners through flashcards. This work has been done on the students of 7th grade of MTs Nurul Islam.…”
Section: Literature Reviewmentioning
confidence: 99%